Comparative Phenotypic and Genotypic Analyses of Salmonella Rissen that Originated from Food Animals in Thailand and United States. (16th June 2014) - Pornsukarom, S.; Patchanee, P.; Erdman, M.; Cray, P. F.; Wittum, T.; Lee, J.; Gebreyes, W. A.
Summary Salmonella enterica serovar Rissen has been recognized as one of the most common serovar among humans and pork production systems in different parts of the world, especially Asia. In the United States, this serovar caused outbreaks but its epidemiologic significance remains unknown. The objectives of this study were to compare the phenotypic (antimicrobial susceptibility) and genotypic attributes of Salmonella Rissen isolated in Thailand (Thai) and the United States (US). All the Thai isolates (n = 30) were recovered from swine faecal samples. The US isolates (n = 35) were recovered from swine faecal samples (n = 29), cattle (n = 2), chicken (n = 2), dog (n = 1) and a ready‐to‐eat product (n = 1). The antimicrobial susceptibility of isolates was determined using the Kirby‐Bauer disk diffusion method with a panel of 12 antimicrobials. Pulse‐field gel electrophoresis (PFGE) was used to determine the genotypic diversity of isolates. All Thai isolates showed multidrug resistance (MDR) with the most frequent antibiotic resistance shown against ampicillin (100%), sulfisoxazole (96.7%), tetracycline (93.3%), streptomycin (90%) and chloramphenicol (30%). About half of the isolates of USA origin were pan‐susceptible and roughly 30% were resistant to only tetracycline (R‐type: Te). Salmonella Rissen isolated from Thailand and the USA in this study were found to be clonally unrelated. Genotypic analyses indicated that isolates were clustered primarily based on the geographic origin implying the limited clonality among the strains. Clonal relatedness among different host species within the same geography (USA) was found. We found genotypic similarity in Thai and US isolates in few instances but with no epidemiological link. Further studies to assess propensity for increased inter‐regional transmission and dissemination is warranted.